DAMPAK PEMINDAHAN IBU KOTA NEGARA TERHADAP PENDUDUK DAN KETENAGAKERJAAN DI PROVINSI JAWA BARAT - Janiar Ningrum; Jamalludin Jamalludin; Izzun Nafiah; Ferry Maurist Sitorus; Ferlistya Pratita Rari; Irma Siti Maryamah (Jurnal Kependudukan Indonesia, 2020)
The plan to relocate the Indonesian capital as set out in the 2020-2024 National Medium-Term Development Plan (RPJMN) to East Kalimantan Province will start in 2024. During the process, the government also plans to move central civil servants to the new capital. The planned relocation of the capital city impacts all central civil servants located in DKI Jakarta and surrounding areas. This research used secondary data sources as a basis for population and employment projections. From the results obtained, West Java's population will continue to grow during the growth rate decline. The relocation plan will directly impact the West Java population, but the effect tends to be less significant given the small number of central civil servants located in west java compared to West Java's population as a whole. The relocation plan will impact social environment conditions, economic activity, and the environment in surrounding areas.